“I Thought It Was Jazz”: Polyphonic Voices in Jazz, Modernism, and the Processes of Institutionalization. - William M. Dabback (Transposition)
This paper examines the movements in jazz in the 1930’s and 1940’s, and centers on the question of awareness regarding the emergence of bebop out of the Swing Era; the social, musical, and economic realities of the time period; and how these issues relate to concepts in modernism. The research includes interviews completed with jazz practitioners who worked during the time period under investigation supplemented with critical literature. Key constructs that emerged included processes of institutionalization, issues of revolution versus evolution in jazz, the role of media in jazz reception, and issues of artistic autonomy and commodification.